Heritability and expression of yield and yield components in cowpea, an underutilized crop in Africa - Matjeke, Milcah Bogaleng; Labuschagne, Maryke Tine; Gerrano, Abe Shegro; Minnaar-Ontong, Adré; Mbuma, Ntombokulunga Wedy (Frontiers in Sustainable Food Systems, 2025)
Grain yield in South Africa cowpea remains low compared to other cowpea producing countries, due largely to a lack of breeding efforts. The objectives of this study were to cross diverse parental genotypes and to measure yield and yield components in the parents and F1 hybrid progeny. Ten cowpea parental genotypes selected for diverse characteristics were assessed for genetic diversity using 20 simple sequence repeat (SSR) markers. Parents were crossed in a half diallel mating design which produced 45 F1 hybrids, and parents and the hybrids were evaluated for grain yield and yield components in four environments (two locations in two seasons). The genetic diversity analysis identified five highly informative markers (SSR6265, SSR6217, SSR6451, SSR6277, and SSR6436, PIC ≥ 0.5) which indicated their usefulness in determining the genetic structure of cowpea. High broad-sense heritability (>0.80) was observed for all traits except for pod width, indicating that a good response to selection can be expected. Although cowpea is a self-pollinating crop, high levels of heterosis were evident for yield and yield components in this study. Six hybrids (IT96D-602 × Glenda, IT96D-602 × Kisumi-mix, IT96D-602 × 98K-5301, ITOOK-1060 × TVU13953, TVU13953 × Glenda, and IT96D-602 × TVU13953) performed significantly better than their parental genotypes for grain yield, showing heterosis and potential for hybrid breeding. Parental genotypes TVU13953 and IT96D-602 were high yielding and could serve as a foundation for subsequent breeding efforts.